2015
DOI: 10.1186/s40781-015-0048-2
|View full text |Cite
|
Sign up to set email alerts
|

Characteristics of Gouda cheese supplemented with fruit liquors

Abstract: This study was conducted in order to evaluate the quality characteristics of Gouda cheeses supplemented with fruit liquor (Prunusmume or Cornus officinalis). Fruit liquor was supplemented to Gouda cheeses during preparation. Changes in chemical composition, lactic acid bacterial population, pH, water-soluble nitrogen, sensory characteristics, and proteolysis were monitored in the prepared ripened cheese. The electrophoresis patterns of cheese proteins, fruit liquor functional component concentrations, and the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

6
7
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 15 publications
(13 citation statements)
references
References 15 publications
6
7
0
Order By: Relevance
“…The ash content of lime coagulated cheese was significantly high (p ≤ 0.05) than alum and steep water coagulated cheeses. This result agrees with Choi et al (2015) and Song et al (1997) who reported a significant (p < 0.05) increase in the ash content of gouda cheese supplemented with PM fruit liquor over the control. The ash content in this study (2.63 to 3.21%) agrees with 2.57 to 3.95% for six Mexican cheeses (Caro et al, 2014).…”
Section: Proximate Composition Of the Cheesesupporting
confidence: 83%
See 3 more Smart Citations
“…The ash content of lime coagulated cheese was significantly high (p ≤ 0.05) than alum and steep water coagulated cheeses. This result agrees with Choi et al (2015) and Song et al (1997) who reported a significant (p < 0.05) increase in the ash content of gouda cheese supplemented with PM fruit liquor over the control. The ash content in this study (2.63 to 3.21%) agrees with 2.57 to 3.95% for six Mexican cheeses (Caro et al, 2014).…”
Section: Proximate Composition Of the Cheesesupporting
confidence: 83%
“…The carbohydrate content ranged from 8.09 to 13.01% with alum having the highest value (13.01%). Similar result was reported by Choi et al (2015) in gouda cheeses.…”
Section: Proximate Composition Of the Cheesesupporting
confidence: 80%
See 2 more Smart Citations
“…Comparing present results with Choi et al (2015), it is possible to say that moisture and ash values were very similar, protein values were higher in eight cheeses studied and all fat values were lower, and all eight pH values were lower than 6.0 while Gouda´s pH varied between 5.24 and 8.20. Narimatsu et al (2003) found the following values in your experiment with Prato cheese: pH 5.41, titratable acidity 0.57, fat 24.89, moisture 48.4, total solids 51.6, protein 18.16, ash 3.73, chlorides 1.63.…”
Section: Based Insupporting
confidence: 49%